2019
DOI: 10.1002/asia.201900769
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Fluorescence Response of Amphiphilic Flapping Molecules in Compressed Monolayers at the Air–Water Interface

Abstract: The air-water interface, which is the boundary of two phases with alarge difference in polarity, gives adistinct environmentc ompared with bulk water or air.S ince the interface provides af ield for various biomolecules to work, it is importantt ou nderstand the molecular behaviors at the interface. Here, polarity-independentf lapping viscosity probes (FLAP) equipped with hydrophobic/hydrophilic substituents have been synthesized and studied at the airwater interface. In situ fluorescence( FL), which is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 56 publications
0
23
0
1
Order By: Relevance
“…Controls of binaphtyl units can be operated in analogue continuous mode and helicity‐inverted digital modes . Various types of molecular manipulations including regulations of photo‐emission upon manipulation of molecular rotor rotation, deformation of flapping molecules, and one‐dimensional supramolecular polymerization of DNA origami pieces were all accomplished with macroscopic mechanical forces. Very recently, a novel concept, submarine emission, has been proposed as a new methodology for molecular manipulation (Figure ) .…”
Section: Perspectives: Molecular Manipulation/tuning By Nanotechnologmentioning
confidence: 99%
“…Controls of binaphtyl units can be operated in analogue continuous mode and helicity‐inverted digital modes . Various types of molecular manipulations including regulations of photo‐emission upon manipulation of molecular rotor rotation, deformation of flapping molecules, and one‐dimensional supramolecular polymerization of DNA origami pieces were all accomplished with macroscopic mechanical forces. Very recently, a novel concept, submarine emission, has been proposed as a new methodology for molecular manipulation (Figure ) .…”
Section: Perspectives: Molecular Manipulation/tuning By Nanotechnologmentioning
confidence: 99%
“…For example, it was experimentally and theoretically confirmed that binding constants of some molecular association systems such as guanidine–phosphate complex are significantly enhanced (by a factor of 10 6 in some cases) over those in bulk water . In addition, lateral compression of monolayers at the dynamic air–water interface can also affect conformations of molecular machines and receptors embedded at the air–water interface, resulting in various functions such as reversible guest captures, molecular plier control, molecular rotor control, molecular flapping, enantiomeric guest selection, and discrimination of nucleic acid bases . Furthermore, functional thin films can be transferred onto solid surfaces by a non‐equilibrium process following interfacial events such as monolayer‐level sol–gel reaction or enzyme accommodation.…”
Section: Dynamic Assembly Involving Non‐equilibrium Processesmentioning
confidence: 99%
“…As another type of photoemission control upon molecular orientation modulation, manipulation and their emission controls of amphiphilic flapping molecules (Figure C) were investigated at the air–water interface, as reported by Nakanishi, Saito, and co‐workers . Alignments of flapping molecules with hydrophobic and hydrophilic substituents are modulated together with their optical properties by altering upon application of lateral pressures.…”
Section: Control Of Molecular Machinesmentioning
confidence: 99%